2009
DOI: 10.1002/stem.21
|View full text |Cite|
|
Sign up to set email alerts
|

Rostro-Caudal Gradual Loss of Cellular Diversity Within the Periventricular Regions of the Ventricular System

Abstract: Neurogenesis occurs constitutively within the periventricular region (PVR) of the lateral ventricles (LV) of the adult mammalian brain. The occurrence of adult neurogenesis within the PVR outside the neurogenic niche of the LV remains controversial, but neural stem cells can be isolated from PVR of the whole ventricular system. The histological basis of this phenomenon including the regional differences of cellular phenotypes within the PVRs is still enigmatic. The occurrence of neurogenesis or manipulable pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(84 citation statements)
references
References 57 publications
7
75
0
2
Order By: Relevance
“…However, further studies are warranted to investigate whether the observed changes in dopaminergic neurogenesis translate into functional changes of the dopaminergic system in the postnatal and/or adult brain. Detailed knowledge of the composition of the midbrain neurogenic niche harboring dopaminergic NPC capacity will eventually help to develop restorative strategies for neurodegenerative diseases such as Parkinson's disease by both recruitment of endogenous progenitor cells from the niche [50][51][52] and improvement of dopaminergic cell graft. Our study, therefore, provides the initial framework for future studies on the molecular mechanisms mediating oxygen regulation of dopaminergic neurogenesis within the midbrain neurogenesis as its natural environment.…”
Section: /Nurr1mentioning
confidence: 99%
“…However, further studies are warranted to investigate whether the observed changes in dopaminergic neurogenesis translate into functional changes of the dopaminergic system in the postnatal and/or adult brain. Detailed knowledge of the composition of the midbrain neurogenic niche harboring dopaminergic NPC capacity will eventually help to develop restorative strategies for neurodegenerative diseases such as Parkinson's disease by both recruitment of endogenous progenitor cells from the niche [50][51][52] and improvement of dopaminergic cell graft. Our study, therefore, provides the initial framework for future studies on the molecular mechanisms mediating oxygen regulation of dopaminergic neurogenesis within the midbrain neurogenesis as its natural environment.…”
Section: /Nurr1mentioning
confidence: 99%
“…Abundant production of new neurons in the adult mammalian brain is limited to the dentate gyrus of the hippocampus and the subventricular zone of the lateral ventricles in the forebrain (Alvarez-Buylla and Lim, 2004;Thored et al, 2007;Frielingsdorf et al, 2004;Hermann et al, 2009;Zhao et al, 2003). Neurogenesis may be evoked in quiescent regions, but the number of persisting new neurons that are generated remains low and consequently the functional recovery of the animals limited (Lindvall et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…6), since it has been demonstrated that there is a rostro-caudal gradual loss of neurogenic potential within the periventricular germinal region. 30 The choice of the mouse as model to study the PPARg and neurogenesis was due to the difficulties to obtain healthy human brain slices, particularly at subventricular level. Figure 6 shows PPARg immunolocalization along the anterior-posterior and dorsal-ventral axes of LV.…”
Section: Pparg Gene Silencing (Sirna)mentioning
confidence: 99%
“…Therefore, it is apparent that PPARg immunoreactivity decreases along the anterior-posterior axis together with the neurogenic potential. 30 In order to correlate the nuclear staining of PPARg to the neurogenic niche, the co-expression of this transcription factor with markers of different stages of neurogenesis was studied (Fig. 7).…”
Section: Pparg Gene Silencing (Sirna)mentioning
confidence: 99%
See 1 more Smart Citation